Physical development of young athletes - students of physical training schools - S.L. Nyankovskyy; O.B. Plastunova (Zaslavsky O.Yu., 2018)
Background. Features of physical development of young athletes - students of physical training schools - remains poorly known. The purpose of the study was to perform a comparative evaluation of physical development of young athletes and schoolchildren in Ukraine, depending on gender and age. Materials and methods. The anthropometric indices of physical development of 1,188 students of physical training schools (777 boys and 411 girls aged 12-17 years) were studied and compared with the "Criteria for assessing the physical development of school-age children" in Ukraine. Results. The indicators of physical development of boy athletes are higher than those of schoolchildren, almost identical in girl athletes and schoolgirls, and in boy athletes, in contrast to girls, are totally increasing with age. Conclusions. Young athletes are characterized by the dominance of medium and high grades of growth, 12-, 15-, 17-year-old boys and 17-year-old girls - greater frequency of harmonious development, older - predisposition to excessive, younger - to insufficient physical development.